The Attribute as a Secondary Part of a Sentence: Structural, Semantic, and Stylistic Aspects (Linguostylistic Studies, 2018)
Proponents of the syntactic tradition and the latest scientific concepts classify the members of the sentence differently, due to different approaches to the interpretation of the specifics and status of these units, determining the principles of their differentiation, and so on. The purpose of the article is to characterize structural-semantic features of the attribute as secondary part of the sentence in the terms of traditional classification, considering modern scientific studies. The article summarizes the differential features of the secondary parts of the sentence. The attribute is a structural-semantic component of the sentence, and it has such classification signs, which reflect correlations between their formally-syntactic, semantic-syntactic, and communicative equivalents. The article determines the structural and semantic features of the attribute as a traditional secondary part of the sentence and argues that the semantics of the attribute covers such characteristics as the evaluation of the qualitative feature of the subject by its action, the attribute of action by the performer, the quantitative attribute by its quantity indexes. Varieties of the attribute classification correspond to such criteria as its structure (extended and non-extended), the ways of expression, and the form of subordinative connection (consistent and inconsistent). Word forms often have syncretic semantics (attribute-specific or attribute-substantive). According to the traditional approach, secondary parts of the sentence are determined by the principle of ‘this or that’. Analysis of the structural-semantic components provides a basis for identification of the syncretism phenomena and allows escaping one-sided interpretation on the basis of the principle of ‘both’. The majority of cases of attributes inconsistency can be classified more logically as syncretic secondary parts of the sentence. The author considers types of attributes by formal and semantic features and the means of their expression. Syncretic members of a sentence have contaminated meanings, in particular subject-attributive, object-attributive, attributive-material, indicating the characteristics of a person or object.
Keywords: member/part of the sentence; attribute; classification criteria; attribute semantics; means of expression